Women in North East India : role and status of Arunachal women - Mandal, Ramkrishna, 1966-; Ete, Minto, 1976- (New Delhi : Mittal, 2010)
Study of socio-economic conditions of Gallong women of West Siang, Upper Subansiri, and East Siang districts of Arunachal Pradesh, India.
Includes bibliographical references (p. [137]-140) and index.
Keywords: Women, Gallong -- Social conditions; Women, Gallong -- Economic conditions; Arunachal Pradesh (India) -- Social conditions; Arunachal Pradesh (India) -- Economic conditions